FLORISTIC AND VEGETATIONAL ASPECTS OF AN INSELBERG IN THE SEMI-ARID REGION OF NORTHEAST BRAZIL - Gomes, P.; Alves, M. (Edinburgh Journal of Botany, 2009)
Inselbergs are rocky environments that support a unique flora distinct from that of the surrounding area. The objectives of this work were to conduct a floristic inventory of an inselberg in the semi-arid region of Northeast Brazil, and to investigate the relationship between its flora and the flora of the surrounding area. The following questions were addressed: is the species richness comparable to other inselbergs in northeastern Brazil; is the floristic composition of the inselberg more similar to other inselbergs or to the surrounding Caatinga vegetation; and do the similarities in the floristic composition of inselbergs depend on the distance between them? This work documents 201 species in 62 families. Cyperaceae (28 spp.), Euphorbiaceae (19), Poaceae (15), Orchidaceae (11) and Bromeliaceae (9) are the most species-rich families. On the inselberg the plants are distributed in islands found on exposed rock, in fissures and in depressions in the rock. Variations in species richness in the region were assessed by comparison of floristic inventories conducted in other inselbergs of the semi-arid region with those of this study. The flora of the inselberg under investigation is more similar to the flora of other nearby inselbergs than to the vegetation of the surrounding semi-arid region.